Inhibition of Neddylation Represses Lipopolysaccharide-induced Proinflammatory Cytokine Production in Macrophage Cells - Chang, Fang-Mei (American Society for Biochemistry and Molecular Biology, 2012)
Cullin-RING E3 ligases (CRLs) are a class of ubiquitin ligases that control the proteasomal degradation of numerous target proteins, including IκB, and the activity of these CRLs are positively regulated by conjugation of a Nedd8 polypeptide onto Cullin proteins in a process called neddylation. CRL-mediated degradation of IκB, which normally interacts with and retains NF-κB in the cytoplasm, permits nuclear translocation and transactivation of the NF-κB transcription factor. Neddylation occurs through a multistep enzymatic process involving Nedd8 activating enzymes, and recent studies have shown that the pharmacological agent, MLN4924, can potently inhibit Nedd8 activating enzymes, thereby preventing neddylation of Cullin proteins and preventing the degradation of CRL target proteins. In macrophages, regulation of NF-κB signaling functions as a primary pathway by which infectious agents such as lipopolysaccharides (LPSs) cause the up-regulation of proinflammatory cytokines. Here we have analyzed the effects of MLN4924, and compared the effects of MLN4924 with a known anti-inflammatory agent (dexamethasone), on certain proinflammatory cytokines (TNF-α and IL-6) and the NF-κB signaling pathway in LPS-stimulated macrophages. We also used siRNA to block neddylation to assess the role of this molecular process during LPS-induced cytokine responsiveness. Our results demonstrate that blocking neddylation, either pharmacologically or using siRNA, abrogates the increase in certain proinflammatory cytokines secreted from macrophages in response to LPS. In addition, we have shown that MLN4924 and dexamethasone inhibit LPS-induced cytokine up-regulation at the transcriptional level, albeit through different molecular mechanisms. Thus, neddylation represents a novel molecular process in macrophages that can be targeted to prevent and/or treat the LPS-induced up-regulation of proinflammatory cytokines and the disease processes associated with their up-regulation.